2018
DOI: 10.3389/fpsyg.2018.01002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mindfulness Training on Proactive and Reactive Cognitive Control

Abstract: Previous studies have demonstrated that mindfulness practice can improve general cognitive control. However, little research has examined whether mindfulness practices affect different cognitive control strategies. According to the dual mechanisms of control (DMC) model, different cognitive control strategies may play distinct roles in individuals’ lives. Proactive control allows people to maintain and prepare for goals, whereas reactive control allows them to respond flexibly to a changing environment. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 51 publications
(79 reference statements)
1
27
2
Order By: Relevance
“…The results showed that there was a significant difference in post-test scores between the experimental and control groups in the scores related to cognitive flexibility, and considering the higher mean scores of the cognitive flexibility of the experimental group in the post-test, it can be stated that mindfulness training was effective in increasing students' cognitive flexibility. The results were in line with similar studies conducted Abdi et al (2016), (Kurmi et al, 2015), Pour Mohammadi and Bagheri (2015), Li et al (2018), Hartkamp and Thornton (2017), Murphy-Beiner and Soar (2020), and (Yadav, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that there was a significant difference in post-test scores between the experimental and control groups in the scores related to cognitive flexibility, and considering the higher mean scores of the cognitive flexibility of the experimental group in the post-test, it can be stated that mindfulness training was effective in increasing students' cognitive flexibility. The results were in line with similar studies conducted Abdi et al (2016), (Kurmi et al, 2015), Pour Mohammadi and Bagheri (2015), Li et al (2018), Hartkamp and Thornton (2017), Murphy-Beiner and Soar (2020), and (Yadav, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the results indicated the effect of mindfulness training on reducing automatic cognitive processing and the fact that automatic cognitive processing is the opposite of cognitive flexibility. In addition, Li, Liu, Zhang, Liu, and Wei (2018) investigated the effect of mindfulness training on preventive and reactive cognitive control. Their research showed that eight sessions of mindfulness training improved people's scores on preventive and reactive cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cognitive control mechanisms have been investigated in people who participated to a MBSR program (Kabat-Zinn 1990), a structured and standardized intervention. In a study (Li et al 2018), the AX-Continuous Performance Task (AX-CPT) paradigm was used. This paradigm tests the dynamic interaction between proactive and reactive cognitive control mechanisms (e.g., Dias et al 2003;Gonthier et al 2016;Morales et al 2015;Richmond et al 2015).…”
Section: For a Review)mentioning
confidence: 99%
“…The task requires to respond to probe stimulus according to the preceding cue stimulus. The study by Li et al (2018) showed a shift toward the use of more proactive control processes in a group engaged in a Mindfulness-Based Cognitive Therapy (MBCT) program. However, no significant interactions emerged when comparing the MBCT with a waiting list control group.…”
Section: For a Review)mentioning
confidence: 99%
“…MBI alleviates psychological distress (e.g., stress, anxiety, mood symptoms) with medium effect sizes compared to waitlist controls (Hedge's gs = 0.41−0.53), and active treatment controls (Hedge's gs = 0.33−0.5) (Hofmann et al, 2010;Khoury et al, 2013). Additionally, preliminary evidence supports that MBI enhances cognitive abilities (e.g., cognitive flexibility, attention, and executive functioning), which might affect social functioning (Lutz et al, 2015;Li et al, 2018;Wielgosz et al, 2019). Some studies suggest that cognitive flexibility promotes effective management of stressful life events, and is associated with good mental health (Kashdan and Rottenberg, 2010;Logue and Gould, 2014).…”
Section: Introductionmentioning
confidence: 96%